The megaport of Chancay and the renaissance of Peru in world trade - De Orbegoso Russell, Carmela (2024)
With the Chancay Megaport project, which is being developed north of Lima and which initially has an investment of US$3.6 billion US dollars, Peru is expected to position itself as one of the main destinations and outlets for world trade, essentially of the Asia-Pacific region. With this private investment, together with high-tech equipment, it is expected to build a high-tech port capable of receiving large ships and cargo vessels, which will increase Peru's commercial and economic expectations in the face of international consensus, since it is expected that manage to capture the attention of investors and large companies. And in all this economic development, a great potential for ancillary and related jobs would also be created that would benefit the economic situation of Peru and the rest of the countries in the region on a large scale. Taking all this into account, the Peruvian State and local governments are involved and incorporated in the effective development of this project of great development for the entire region, to which they must pay special attention due to the magnitude and importance of the construction of the infrastructure that the city of Chancay is receiving, because it is evident that the Chancay Megaport project represents a great economic opportunity for different sectors of our country.